Imprinting Ferromagnetism and Superconductivity in Single Atomic Layers of Molecular Superlattices. Issue 25 (17th May 2020) - Li, Zejun; Zhang, Xiuying; Zhao, Xiaoxu; Li, Jing; Herng, Tun Seng; Xu, Haomin; Lin, Fanrong; Lyu, Pin; Peng, Xinnan; Yu, Wei; Hai, Xiao; Chen, Cheng; et al.
Abstract: Ferromagnetism and superconductivity are two antagonistic phenomena since ferromagnetic exchange fields tend to destroy singlet Cooper pairs. Reconciliation of these two competing phases has been achieved in vertically stacked heterostructures where these two orders are confined in different layers. However, controllable integration of these two phases in one atomic layer is a longstanding challenge. Here, an interlayer‐space‐confined chemical design (ICCD) is reported for the synthesis of dilute single‐atom‐doped TaS2 molecular superlattice, whereby ferromagnetism is observed in the superconducting TaS2 layers. The intercalation of 2H‐TaS2 crystal with bulky organic ammonium molecule expands its van der Waals gap for single‐atom doping via co‐intercalated cobalt ions, resulting in the formation of quasi‐monolayer Co‐doped TaS2 superlattices. Isolated Co atoms are decorated in the basal plane of the TaS2 via substituting the Ta atom or anchoring at a hollow site, wherein the orbital‐selected p–d hybridization between Co and neighboring Ta and S atoms induces local magnetic moments with strong ferromagnetic coupling. This ICCD approach can be applied to various metal ions, enabling the synthesis of a series of crystal‐size TaS2 molecular superlattices. Abstract : Ferromagnetism is successfully introduced in superconducting TaS2 molecular superlattices with single Co atom doping, which is achieved by an interlayer‐space‐confined chemical design (ICCD). This ICCD approach can be applied to various metal ions, opening up new avenues for designing artificial 2D material superlattices with exotic phases and desired functionalities.